Effect of Sunflower Seeds on Hypercholesterolemia, Fatty Liver, Fasting Blood Glucose in Diabetes Mellitus Type 2 Patients: The potential benefits of sunflower seeds in managing type 2 diabetes and improving cardiovascular health (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The objective of the current study was to evaluate and analyse the effect of sunflower seeds on fasting blood glucose (FBS) in patients with type 2 diabetes mellitus. In the study, 60 patients were enrolled, split between the case and the control group. For these patients, different anthropometric measurements (height, weight, blood pressure) and biochemical parameters (cholesterol, triglycerides, low-density lipoprotein [LDL], high-density lipoprotein [HDL] and fasting blood glucose [FBS]) were recorded for 6 months before and after sunflower seed supplementation. Compared with the control group, patients taking sunflower seeds showed a positive and faster decrease in their level of FBS. The blood glucose level decreased from 186.2 mgdl to 109.9 mgdl in the case group, while it decreased from 163.3 mgdl to 119.2 mgdl in the control group. As a household and natural remedy, sunflower seeds may be recommended to control blood sugar levels in patients with type 2 diabetes. It also leads to a good rise in levels of HDL (good cholesterol), which helps maintain the health of the heart.